1998
DOI: 10.1007/s00585-998-0986-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the ionospheric E and F regions over Europe

Abstract: Abstract. Continuous observations in the ionospheric E and F regions have been regularly carried out since the ®fties of this century at many ionosonde stations. Using these data from 31 European stations long-term trends have been derived for dierent parameters of the ionospheric E layer (h¢ E, foE), F1 layer (foF1) and F2 layer (hmF2, foF2). The detected trends in the E and F1 layers (lowering of the E region height h¢E; increase of the peak electron densities of the E and F1 layers, foE and foF1) are in qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
139
4
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 10 publications
9
139
4
1
Order By: Relevance
“…Rishbeth and Roble [1992] also predicted an increase in the peak electron density in the E layer, corresponding to an increase in f o E of 0.05-0.08 MHz. This theoretical prediction, and the experimental results obtained by Bremer [1998Bremer [ , 2004Bremer [ , 2008, Danilov [2002], and Mikhailov [2006], of a positive trend in f o E made us suspect that Sq should also present a positive trend.…”
Section: Trends Due To Increasing Greenhouse Gas Concentrationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Rishbeth and Roble [1992] also predicted an increase in the peak electron density in the E layer, corresponding to an increase in f o E of 0.05-0.08 MHz. This theoretical prediction, and the experimental results obtained by Bremer [1998Bremer [ , 2004Bremer [ , 2008, Danilov [2002], and Mikhailov [2006], of a positive trend in f o E made us suspect that Sq should also present a positive trend.…”
Section: Trends Due To Increasing Greenhouse Gas Concentrationsmentioning
confidence: 87%
“…On the other hand, the increase in greenhouse gas concentrations, expected to produce an increase in the peak value of the electron concentration in the E region ( f o E) [Rishbeth and Roble, 1992;Bremer, 1998Bremer, , 2004Bremer, , 2008, should also be expected to induce some effect on Sq.…”
Section: Introductionmentioning
confidence: 99%
“…However an analysis has shown that the worldwide pattern of the F2 and E-layer parameter long-term trends is very complicated and cannot be explained suciently by this eect. Further analysis by Bremer (1998) of many European ionosonde stations and by Upadhyay and Mahajan (1998) of a global set of ionosonde stations has shown that the F2-layer parameter trends turn out to be dierent both in sign and magnitude for dierent stations and this cannot be reconciled with the greenhouse hypothesis. A contradiction with this hypothesis was revealed also by Leshchenko (1996, 1998) when analyzing the foE long-term trends.…”
Section: Introductionmentioning
confidence: 83%
“…Long-term variations (trends) of the upper atmosphere and ionosphere parameters are widely discussed in recent publications due to the problem of global climate changes (see reviews by Danilov, 1997Danilov, , 1998Leshchenko, 1994, 1995;Ulich and Turunen, 1997;Rishbeth, 1997;Mikhailov, 1998, 1999;Bremer, 1992Bremer, , 1998Upadhyay and Mahajan, 1998). After the model calculations of Rishbeth (1990) and Rishbeth and Roble (1992) predicting the ionospheric eects of atmospheric greenhouse gas concentration increase, the researchers have been trying to relate the observed long-term trends in the ionospheric parameters to this greenhouse eect (Bremer, 1992;Givishvili and Leshchenko, 1994;Ulich andTurunen, 1997, Jarvis et al, 1998;Upadhyay and Mahajan, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…There are also inconsistencies between the reported magnitudes of long-term trends in ion temperature and neutral density, which still need to be reconciled (Akmaev 2012). In addition, several ionosonde stations show increases in the height of the peak of the F 2 layer, h m F 2 , rather than the expected decrease (Bremer 1998;Upadhyay & Mahajan 1998), and many stations show significant trends in the critical frequency of the F 2 layer, f o F 2 (Upadhyay & Mahajan 1998;Elias & Ortiz de Adler 2006), which is directly related to the maximum electron density of the F 2 layer, N m F 2 (N m F 2 / (f o F 2 ) 2 ). These discrepancies with the predicted effects of enhanced CO 2 levels mean that other drivers of long-term change may be important also.…”
Section: Introductionmentioning
confidence: 96%